Loxoprofen-induced interstitial pneumonia: a case report. (December 2016) - Kato, Motoyasu; Sasaki, Shinichi; Sekimoto, Yasuhito; Arano, Naoko; Jo, Hitomi; Suina, Kentaro; Kuriyama, Sachiko; Muraki, Keiko; Nagashima, Osamu; Yoshioka, Yasuko; Tominaga, Shigeru; Takahashi, Kazuhisa
Abstract Background Loxoprofen is a nonsteroidal anti-inflammatory drug used in the treatment of many diseases. However, there are no case reports about loxoprofen-induced pneumonia. We have encountered a rare case of loxoprofen-induced pneumonia. Case presentation We report the case of a 71-year-old Japanese woman who was initially treated with loxoprofen for fever. She was admitted to our hospital because of worsening of her symptoms, including fever and dyspnea. Her symptoms improved after treatment with ceftriaxone. Seven days after admission, she again developed high fever. She was again treated with loxoprofen and levofloxacin. However, acute respiratory failure developed after initiation of loxoprofen treatment. Chest computed tomography showed peribronchovascular consolidation. She was diagnosed with loxoprofen-induced pneumonia for which she was administered steroids. After treatment, her dyspnea and radiological findings improved. Conclusions The findings in this case report reveal an association between treatment with a nonsteroidal anti-inflammatory drug and pneumonia. This rare case was diagnosed after accidental retreatment with loxoprofen. This is the first report of loxoprofen-induced pneumonia.